Cross-cultural communication how culture affects communication - Mcllwain, Charlton; Mitler, Cynthia; Collins, Sue; Odyssey Productions (New York N.Y. : Insight Media [distributor], 2005)
Issues in cross-cultural communication are examined including public behavior, taboos, power, stereotyping, time conceptualization, socialization, direct and indirect communication and high context versus low contesxt cultures
Title from title screen
Keywords: Intercultural communication; Communication and culture; Communication; Cross-cultural counseling; Sociology